1997
DOI: 10.1021/jp9711306
|View full text |Cite
|
Sign up to set email alerts
|

EPR Studies of the Dynamics of Rotation of Dioxygen in Model Cobalt(II) Hemes and Cobalt-Containing Hybrid Hemoglobins

Abstract: Earlier we showed that the shapes of the EPR spectra of cobalt(II) porphyrinate(nitrogen base)(dioxygen) complexes in fluid solution were sensitive to the rate of rotation about the Co−O bond (Walker, F. A.; Bowen, J. H. J. Am. Chem. Soc. 1985, 107, 7632). We have now extended these studies to four metal-substituted hybrid hemoglobins in an attempt to determine whether EPR spectroscopy is sensitive to differences in the mobility of dioxygen in the α and β subunits of the T and R quaternary states. For purposes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 46 publications
8
44
0
Order By: Relevance
“…The g and 59 Co hf-tensor values of the Co(III)OEP • py • Oz' complex and its deoxy precursor have been obtained from the spectra (see Table 4). The values are in good agreement with those found by van Doorslaer and Schweiger [10] and also Bowen et al [11] for the oxygenated CoTPP complex, who also pointed out temperature-dependent changes of the g anisotropy due to oxygen rotation at liquid-nitrogen temperature (100 -200 K).…”
Section: Epr Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The g and 59 Co hf-tensor values of the Co(III)OEP • py • Oz' complex and its deoxy precursor have been obtained from the spectra (see Table 4). The values are in good agreement with those found by van Doorslaer and Schweiger [10] and also Bowen et al [11] for the oxygenated CoTPP complex, who also pointed out temperature-dependent changes of the g anisotropy due to oxygen rotation at liquid-nitrogen temperature (100 -200 K).…”
Section: Epr Resultssupporting
confidence: 91%
“…From this information one can, in principle, obtain the location of the nuclei around the spin-carrying metal center (distance greater than 0.2 nm) [34,38] by use of the point-dipole approximation as demonstrated earlier for axially ligated Cu(II) and Co(II) complexes [39][40][41][42][43]. More recently cw and pulsed multifrequency EPR and ENDOR studies of Co(II) tetraphenylporphyrin complexes (CoTPP) with imidazol and pyridine as axial ligands as well as their superoxo complexes have been published [8][9][10][11]. In this paper we use multinuclear (cw) ENDOR performed on Co(II) octaethylporphyrin (CoOEP) with various ligands as a model (Fig.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The EPR measurements show however that this complex is also already fully oxygenated at 240 K in contrast to earlier observations for ™simple∫ Co II porphyrins. [25,27,28] Finally, the present study clearly shows that high O 2 affinity and the presence of functional groups capable of H-bond donation in synthetic iron(II) and cobalt(II) porphyrins does not guarantee the stabilization of dioxygen by an H-bond. It forms a challenge for metalloporphyrin synthetic chemistry to design new classes of iron(II) porphyrins where the H-bond is ™forced∫ upon the dioxygen fragment by steric constraints to truly mimic the heme in its natural protein environment.…”
Section: Nitrogen Interactionsmentioning
confidence: 64%
“…Earlier studies on toluene solutions of oxygenated cobalt(II) complexes showed that the EPR spectrum changes continuously with increasing temperature from 140 to 240 K. [27,28] This reflects the increased motion of both the dioxygen fragment and the entire molecule, which averages the anisotropic part of the spectrum. In the limit of fast isotropic motion, the EPR spectrum consists of eight narrow lines, centered around g iso ( 1…”
Section: Cw Epr Spectramentioning
confidence: 95%